Experimental investigations on suitability of polypropylene (PP) and ethylene vinyl acetate (EVA) in additive manufacturing. (2018) - Kumar, Narendra; Jain, Prashant K.; Tandon, Puneet; Mohan Pandey, Pulak
Abstract: The range of materials in the form of the filament is limited for commercial Fused Deposition Modelling (FDM) systems due to the specific requirements of size and shape of the filament. Instead of filament shape, use of pellets as the raw material might be increased the application domain of FDM system, as different types of the thermoplastic pellets are commercially available. Since commercial FDM system deals with filament form material consequently, the modification in the existing system is to be required to process the pellet form materials, which is not an easy task. Therefore, in this paper, suitability analysis of Polypropylene (PP) and Ethylene Vinyl Acetate (EVA) materials have been conducted by customized developednovel Material Deposition Tool (MDT) system.The considered materials have many industrial applications but the potential of these materials has not been explored yet in the commercial additive manufacturing systems. Experiments have been conducted and results show that the selected materials are suitable for the use in the additive manufacturing.